2014
DOI: 10.1042/bj20140463
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional consequences of removing the N-terminal domain from the magnesium chelatase ChlH subunit of Thermosynechococcus elongatus

Abstract: Magnesium chelatase (MgCH) initiates chlorophyll biosynthesis by catalysing the ATP-dependent insertion of Mg2+ into protoporphyrin. This large enzyme complex comprises ChlH, I and D subunits, with I and D involved in ATP hydrolysis, and H the protein that handles the substrate and product. The 148 kDa ChlH subunit has a globular N-terminal domain attached by a narrow linker to a hollow cage-like structure. Following deletion of this ~18 kDa domain from the Thermosynechoccus elongatus ChlH, we used single part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…It was reported that CHLH predominantly exists as a monomer in solution (Qian et al, 2012), whereas a loosely bound CHLH dimer was observed in the crystal. The dimerization interface are domains I and V, which is consistent with a previous study that removal of the N-terminal 159 residues of T. elongates ChlH facilitates a monomeric state (Adams et al, 2014). The porphyrin-binding internal pocket is proposed to be located at the interface between domains III and V, a region with the most conserved residues.…”
Section: Introductionsupporting
confidence: 91%
“…It was reported that CHLH predominantly exists as a monomer in solution (Qian et al, 2012), whereas a loosely bound CHLH dimer was observed in the crystal. The dimerization interface are domains I and V, which is consistent with a previous study that removal of the N-terminal 159 residues of T. elongates ChlH facilitates a monomeric state (Adams et al, 2014). The porphyrin-binding internal pocket is proposed to be located at the interface between domains III and V, a region with the most conserved residues.…”
Section: Introductionsupporting
confidence: 91%
“…It also appears that Gun4 proteins from virtually all sources stimulate MgCh activity via an interaction with the ChlH subunit and bind porphyrins with the highest affinity to MgP (14,16,17). The essential role of porphyrin binding for Gun4 function can be suggested from amino acid alignments (13) because residues in the proposed MgP binding site (␣6/␣7 loop residues, Arg-214, and Asn-211) are conserved through evolution from cyanobacteria to plants.…”
Section: Mechanism Of Porphyrin Binding To the Gun4 Protein-gun4mentioning
confidence: 99%
“…There is evidence that Gun4 physically interacts with ChlH (11,14,17), which is the porphyrin-binding MgCh subunit that presumably also contains the active site for chelation (18). Available in vitro kinetic data imply that Gun4 stimulates MgCh by substantially reducing the P IX and Mg 2ϩ concentrations required for catalysis (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MgCHs require at least three subunits; chlorophyll producing organisms have ChlI (~35 kDa), ChlD (~75 kDa) and ChlH (~150 kDa), and the closely related proteins from bacteriochlorophyll producing organisms are BchI, BchD, and BchH 7, 8 . In cyanobacteria and higher plants a fourth regulatory subunit, Gun4, is required for full protein activity [9][10][11] .The genes for MgCH were originally identified and recombinant protein expression systems were developed some time ago 7,12 , and extensive kinetic characterization of the MgCH has identified the roles of the subunits [13][14][15][16][17][18] . The current mechanistic and structural data suggest a model for the MgCH mechanism where the two AAA + subunits form the ChlID complex 16,19 .…”
mentioning
confidence: 99%